Preparing for life : the complete guide for transitioning to adulthood for those with autism and Asperger's Syndrome - Baker, Jed. 4 0 16; 5 (Arlington, Texas : Future Horizons, 2005)
A life skills guide for individuals with autism and Asperger's syndrome discusses social skills and strategies needed for success in the adult world, including discussion of perspective-taking, nonverbal communication skills, and stress management.
Includes bibliographical references.
Adult.
Keywords: 2 -- 0; 6; Youth with autism spectrum disorders;Autism.;Autistic children -- Life skills guides.;Life skills guides; 20; 2